The cinema of Oliver Stone : art, authorship and activism (2016)
From the outset, the research and writing for this book have ben- efited from an ongoing and intimate collaboration with the film- maker. On one level, this depth of engagement from Oliver Stone should come as no surprise. All through his career, Stone has shown willingness – and indeed a deep interest – in engaging with academic and journalistic debate about his films and their contex- tual significance. For him, being actively involved in the afterlife of a movie and the discussions that it generates is part and parcel of the filmmaker’s responsibility. For example, he directly accepted an engagement with the American Historical Association concerning its debates over the merits of JFK and Nixon, recorded in Robert Brent Toplin’s Oliver Stone’s USA. He also was involved in detailed discussions about the academic commentary on Alexander out- lined in Paul Cartledge and Fiona Rose-Greenland’s Responses to Oliver Stone’s Alexander. However, Stone went even further with our project. He gave his time and energy over a significant period, thus committing his life and work to the long-term and sustained investigation of him and his films. He provided hours of interview time over many meet- ings, roughly within the space of five years of his working life. To assist with this process, we wrote up pre-interview notes outlining the issues to be covered at each session. In response, Stone never arrived unprepared.